The distribution of monoamine oxidase and α-glycerophosphate dehydrogenase in pig brain - Tipton, K. F. (1968)
Activities of the enzymes monoamine oxidase (EC 1.4.3.4), α-glycerophosphate dehydrogenase (EC 1.1.99.5) and cytochrome oxidase (EC 1.9.3.1) were determined in homogenates and in the mitochondrial fraction prepared from individual regions of pig brain. The variation in the activity of α-glycerophosphate dehydrogenase paralleled that of cytochrome oxidase, but this was not the case with monoamine oxidase. The differences in the activities of the enzymes among homogenates of the various regions of the brain persisted in mitochondria prepared from these homogenates. The purification of these three enzymes paralleled each other when mitochondria were prepared, suggesting that the three enzymes are bound to the same particles.